No longer in doubt: Discovery of a second specimen corroborates the validity of Anolis incredulus Garrido and Moreno 1998 (Reptilia, Iguania) - Queiroz, Kevin De; Huie, Jonathan M.; Langan, Esther M. (Zootaxa, 2023)
The species Anolis incredulus was proposed based on a single, poorly preserved specimen from the Sierra Maestra (mountain range) of southeastern Cuba. As its name suggests, this species was considered likely to raise doubts when it was first proposed, and it has been explicitly treated by some recent authors as a species inquirenda (a species of doubtful identity). Here we report on a second specimen of Anolis incredulus discovered in the amphibian and reptile collection of the National Museum of Natural History (Smithsonian Institution) that was collected more than 100 years before the holotype. We describe this specimen in detail and compare it both with the description of the holotype of A. incredulus and with presumed closely related Cuban species, providing evidence that it matches closely with the former and is distinct from the latter, thus corroborating the status of A. incredulus as a valid species. We also score and measure the specimen for sets of morphological characters to make inferences about its phylogenetic relationships and ecology (structural habitat use). Our results indicate that Anolis incredulus is likely a member of a clade of mostly Cuban twig-anole species and that it is a member of the twig ecomorph category, although its reported green coloration suggests either an erroneous ecomorph assignment or a difference in color from that of most other species of Cuban twig anoles.